Efektivitas Pemungutan dan Strategi Pengembangan Pajak Hotel dan Restoran di Kabupaten Kotabaru - Kadir Kadir; Doni Stiadi (JURNAL BISNIS DAN PEMBANGUNAN, 2017)
The purpose of this study to synchronize between the potential to planning. The purpose in particular is to calculate and analyze the potential of the hotel and restaurant tax, calculate and analyze the effectiveness of tax collection of hotels and restaurants, and deliver development strategy hotel and restaurant tax in Kotabaru district.This study was designed to approach descriptive analysis to describe and analyze the potential tax revenues of hotels and restaurants in the district of Kotabaru. Survey conducted on 24 hotels and 165 restorant. Data were analyzed using models of computation approach and the potential effectiveness of hotel and restaurant taxes.The results showed that the hotel tax potential per year higher than the average budget hotel tax years 2010 to 2015, or by only 36.46% of the existing potential. Similarly, when compared to the budget 2015, only 47.42% of the existing potential. Potential restaurant tax per year is higher than the average budget restaurant tax from 2010 to 2015, or only 26.49% of the existing potential. Keywords: collection, effectiveness, hotel, restaurant, strategy, tax